THE EXAMPLES OF EARTHQUAKE PREPARATION IN KAMCHATKA AND JAPAN - Sobolev G.A. (My University, 2001)
A recently proposed predictive parameter RTL was tested using seismological catalogues of Kamchatka and Japan. We analysed three earthquakes in Kamchatka with M>7 and disastrous Hyogo-ken Nanbu (Kobe) earthquake in Japan with M=7.2. It was found that a seismic quiescence had taken place during a period of three years before these earthquakes and been followed by foreshock activation. The dimensions of the quiescence areas reached the first hundreds of kilometers, whereas the epicenters of strong events were located on the edge of quiescence anomalies. The areas of foreshock activation were about 50–100 km, and strong events occurred in the region of maximum anomalies. The number of clusters increased comparatively to the background events during the stages of foreshock activation in epicenter areas of strong earthquakes. The results strengthen the physical basis of earthquake prediction.